Application of Rigidity‐Controlled Supramolecular Affinity Materials for the Gravimetric Detection of Hazardous and Illicit Compounds. Issue 9 (29th July 2016) - Pyka, Isabella; Ryvlin, Dimitrij; Waldvogel, Siegfried R.
Abstract: The combination of an (−)‐isosteviol‐derived building block and 9, 9'‐spirobifluorene or tetraphenylmethane generated highly potent new affinity materials for the detection of volatile organic compounds (VOCs). Comparison of their affinity behaviour with different core structures showed remarkable influence on selectivity and sensitivity due to structural rigidity and their pre‐organization. Their unique supramolecular properties were investigated in an affinity assay using high fundamental frequency quartz crystal microbalances. Abstract : The rigid nature of the core determines the performance of affinity materials for tracing volatile organic compounds. A distinct difference was found between tetraphenylmethane and 9, 9'‐spirobifluorene. The comparison of the affinity behaviour with different core structures showed remarkable influence on selectivity and sensitivity owing to structural rigidity and their pre‐organization (see figure). Less conformational freedom leads to superior detection properties.